2018
DOI: 10.1021/acsnano.7b07377
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytically Active Superstructures of Quantum Dots and Iron Porphyrins for Reduction of CO2 to CO in Water

Abstract: This paper describes the use of electrostatic assemblies of negatively charged colloidal CuInS/ZnS quantum dot (QD) sensitizers and positively charged, trimethylamino-functionalized iron tetraphenylporphyrin catalysts (FeTMA) to photoreduce CO to CO in water upon illumination with 450 nm light. This system achieves a turnover number (TON) of CO (per FeTMA) of 450 after 30 h of illumination, with a selectivity of 99%. Its sensitization efficiency (TON per Joule of photons absorbed) is a factor of 11 larger than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
119
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(120 citation statements)
references
References 52 publications
1
119
0
Order By: Relevance
“…Forinstance,the positively charged CO 2 reduction cocatalysts of trimethylamino-functionalized iron tetraphenylporphyrin (FeTMA) were assembled with negatively charged CuInS 2 / ZnS QDs under mild conditions (Figure 4b,i nset). [37] Under the optimal conditions,the system evolved CO with aTON of 450 per catalyst after 30 hi llumination and as electivity of 99 % (Figure 4b). As aresult of the ultra-fast and consecutive electron transfer from multiple QDs to as ingle FeTMA cocatalyst, the sensitization efficiency( TONp er Joule of photons absorbed) of the assembled system was afactor of 11 larger than that of the uncharged CuInS 2 /ZnS QDs/FeTMA physical mixture in DMSO.N otably,m ost of the photosystems reported so far can only reduce CO 2 to CO.F urther study to realize highly effective and selective conversion of CO 2 into deep reduction products (e.g.,m ethanol and methane) is highly desirable.R ecently,W eiss et al revealed that the promoted excitonic energy transfer in the electrostatic interaction induced QD assembly could also effectively enhance the efficiencyofs olar-to-H 2 evolution.…”
Section: Electrostatic Interaction Induced Qd Assemblymentioning
confidence: 99%
“…Forinstance,the positively charged CO 2 reduction cocatalysts of trimethylamino-functionalized iron tetraphenylporphyrin (FeTMA) were assembled with negatively charged CuInS 2 / ZnS QDs under mild conditions (Figure 4b,i nset). [37] Under the optimal conditions,the system evolved CO with aTON of 450 per catalyst after 30 hi llumination and as electivity of 99 % (Figure 4b). As aresult of the ultra-fast and consecutive electron transfer from multiple QDs to as ingle FeTMA cocatalyst, the sensitization efficiency( TONp er Joule of photons absorbed) of the assembled system was afactor of 11 larger than that of the uncharged CuInS 2 /ZnS QDs/FeTMA physical mixture in DMSO.N otably,m ost of the photosystems reported so far can only reduce CO 2 to CO.F urther study to realize highly effective and selective conversion of CO 2 into deep reduction products (e.g.,m ethanol and methane) is highly desirable.R ecently,W eiss et al revealed that the promoted excitonic energy transfer in the electrostatic interaction induced QD assembly could also effectively enhance the efficiencyofs olar-to-H 2 evolution.…”
Section: Electrostatic Interaction Induced Qd Assemblymentioning
confidence: 99%
“…Taken together, a water‐soluble conjugated small molecule would be a favorable choice to overcome these drawbacks . In this case, unfortunately, the loading of cocatalyst on a single‐molecule catalyst is relatively difficult due to the limited interface contact area . As a result, the diffusion‐controlled bimolecular electron transfer process between the individually separated small‐molecule catalyst and cocatalyst becomes the bottleneck to achieve high photocatalytic efficiency …”
Section: Introductionmentioning
confidence: 99%
“…b) Plot of TON vs. absorbed photon energy (bottom axis) and vs. illumination time (top axis) reproduced from Ref. with the permission from ACS.…”
Section: Qd Assembly For Multielectron Reactionsmentioning
confidence: 99%